ESTIMA Journal: 15 Years of History and New Advances (Estima – Brazilian Journal of Enterostomal Therapy, 2018)
For 15 years ago ESTIMA Journal began with the purpose, at that time, to become the official communication vehicle of Brazilian Stomatherapy Association (SOBEST) and to edit/ publish topics relevant to the education or improvement of SOBEST members and health professionals involved with Stomatherapy (...)